HINDU SPIRITUAL GROUPS IN INDONESIA AND THEIR ACTIVE ROLES IN MAINTAINING HARMONY - I Nyoman Yoga Segara (Balai Penelitian dan Pengembangan Agama Semarang, 2018)
Hinduism in Indonesia has been embraced in various ways. In addition to individual adoption, the conversion to Hinduism has also be performed through religious groups, which later develop by adjusting the local customs. The distinction between one adherent to another is essentially unified by the same theology. Panca Sraddha is one of the binders of Buddhis’ belief to Brahman, Atman, Karmaphala, Punarbhawa or Samsara, and Moksa. By utilizing this similarity, people who belong to Hinduism in Indonesia can live in harmony with other fellow Hindus as well as other religious communities, including Indonesian